Komunikasi Krisis dan Pengaruhnya Terhadap Kepercayaan Konsumen: Studi pada Krisis Produk Mie Instan Indofood (2023) - Nia Mintari; Lorence Manalu; Masduki Asbari; Nofiyanti Nofiyanti; Dian Ayunita; Aulia Rizka; Taufiq Kimas (Motivaksi: Jurnal Ilmu Sosial, Manajemen, Akuntansi dan Bisnis, 2025)
This study aims to analyze the crisis communication strategy implemented by Indofood in dealing with the crisis involving the Indomie Special Chicken Flavor product in 2023, related to the discovery of ethylene oxide (EtO) content that exceeds the safe limit. This study evaluates the effectiveness of crisis communication, analyzes consumer responses, and the application of crisis communication theory, especially the Situational Crisis Communication Theory (SCCT). This study uses a descriptive qualitative method with secondary data collected through literature studies, press releases, social media, and official statements from Indofood and BPOM. The results of the study indicate that Indofood implemented a diminishment and rebuilding strategy to reduce the impact of the crisis in the Indonesian domestic market and improve its brand image in the international market. The use of more interactive and empathetic social media is needed to build emotional relationships with more skeptical international consumers. This study concludes that proactive and responsive communication is essential in restoring consumer trust and maintaining brand loyalty, especially in the international market. This study contributes to understanding the dynamics of crisis communication in the food industry and the importance of an effective communication strategy in maintaining a company's reputation.